Сучасна українська масова література крізь призму творчої індивідуальності Андрія Кокотюхи - Бригадир, Ярослава; Brygadyr, Yaroslava (Східноєвропейський національний університет імені Лесі Українки, 2015)
Статтю присвячено аналізу стану сучасної української масової літератури, висвітлено основні категорії масліту. Розглянуто творчість Андрія Кокотюхи в контексті становлення сучасної української масової літератури, а також, що важ- ливо, порушено питання формування власне українського культурного простору.The article is devoted to the main categories of modern popular literature. It also focused on the concepts of readability, screen, formality, canon of the genre, template, bestseller. Scientific assessments made by the most leading researchers of modern literary process have presented; the distinction between elite and mass literature have substantiated and the place of massliterature in today socio-cultural sphere have also determined The creation of Andriy Kokotyuha is considered in the context of modern Ukrainian popular literature, and what is important, the question of forming of Ukrainian cultural space is also raised.
The Creation of Andriу Kokotyuha as an Example of Modern Ukrainian Popular Literature
Keywords: сучасна українська масова література; жанровий канон; естетичний шаблон; ідеологічний стереотип; modern Ukrainian mass literature; elite literature; popular literature; canon of the genre; bestseller; readability; aesthetic pattern; ideological stereotype; cultural product; information policy